The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4269/ajtmh.13-0511
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Genotypic Distribution of Orientia tsutsugamushi Strains Causing Human Infections on Jeju Island

Abstract: Abstract. We investigated the clinical characteristics and serologic types of tsutsugamushi disease on the largest island of South Korea. There were 141 patients with tsutsugamushi disease at Jeju National University Hospital and Seogwipo Medical Center between November of 2003 and December of 2012. Median age of patients was 61 years, and 59% were women. The major clinical manifestations were fever (80.5%) and skin rash (55.7%), with eschars evident in 75

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…30,31 A maculopapular rash, as a presenting feature, was seen in 9% of our patients, as compared with 22% patients from Vellore, 20% patients from the Himalayan region of north India, 30% patients in Thailand, and 55.7% patients from Jeju Islands, South Korea. [23][24][25][26][27][28][29][30][31][32] In the present study, splenomegaly was present in 45% of patients. Another study from north India has reported a higher splenomegaly rate of 59%.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…30,31 A maculopapular rash, as a presenting feature, was seen in 9% of our patients, as compared with 22% patients from Vellore, 20% patients from the Himalayan region of north India, 30% patients in Thailand, and 55.7% patients from Jeju Islands, South Korea. [23][24][25][26][27][28][29][30][31][32] In the present study, splenomegaly was present in 45% of patients. Another study from north India has reported a higher splenomegaly rate of 59%.…”
Section: Discussionmentioning
confidence: 80%
“…[12][13][14][15][16][17][18][19][20][21][22] The pathognomonic eschar was present in 14% patients (Table 3), a figure considerably higher than a previous study from the Himalayan region (9.5% patients), but lesser than that reported from south India (43.5%) and Jeju Island in South Korea (75.8%). 26,28,29 This variation in the presence of eschar may be explained by the geographic distribution of different strains of the organism. Lymphadenopathy, present in a nearly 11% third of our patients, was also lesser than in the studies from Vietnam and Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…In the present cases, death and serious complications including pneumonia, acute kidney injury, and encephalitis were not observed. The previous study at a university hospital that was located in Jeju-si also reported that death among the 138 patients was not observed [33]. Furthermore, the low mortality was achieved in the present patients that included a large number of elderly patients and patients with comorbid conditions.…”
Section: Discussionmentioning
confidence: 55%
“…Physicians may not consider Q fever in the differential diagnosis in patients with acute febrile illness because the symptoms and signs of Q fever are nonspecific; acute fever is common due to severe fever with thrombocytopenia syndrome (in the spring and the summer) and scrub typhus (in the autumn) in individuals who participate in outdoor activity [ 23 , 24 , 25 , 26 ], and most infected individuals have no history of animal contact or occupational exposure [ 27 ].…”
Section: Discussionmentioning
confidence: 99%